2022
DOI: 10.3390/jpm12091385
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Validation of Risk Alleles in Genetic Addiction Risk Severity (GARS) Test: Early Identification of Risk for Alcohol Use Disorder (AUD) in 74,566 Case–Control Subjects

Abstract: Since 1990, when our laboratory published the association of the DRD2 Taq A1 allele and severe alcoholism in JAMA, there has been an explosion of genetic candidate association studies, including GWAS. To develop an accurate test to help identify those at risk for at least Alcohol Use Disorder (AUD), Blum’s group developed the Genetic Addiction Risk Severity (GARS) test, consisting of ten genes and eleven associated risk alleles. In order to statistically validate the selection of these risk alleles measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Pearson's χ 2 test or Fisher's exact test was applied to compare the gender, genotype, and allele distribution if available. The statistical analyses found the OR, 95% CI for OR, and the post risk for 8% estimation of the population's alcoholism prevalence revealed a significant detection [88]. It is relevant that while the GARS test does not actually stratify low, median, or high preaddiction status, the newly developed RDSQ29, which has been validated [117], could be utilized in combination with the GARS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pearson's χ 2 test or Fisher's exact test was applied to compare the gender, genotype, and allele distribution if available. The statistical analyses found the OR, 95% CI for OR, and the post risk for 8% estimation of the population's alcoholism prevalence revealed a significant detection [88]. It is relevant that while the GARS test does not actually stratify low, median, or high preaddiction status, the newly developed RDSQ29, which has been validated [117], could be utilized in combination with the GARS.…”
Section: Discussionmentioning
confidence: 99%
“…These alleles were proposed for a GARS panel in case-control studies, specifically for alcoholism (Table 1) [see ref. [88] for further explanation]. Other studies also demonstrated that this could be associated with the impulsivity and aggression of AUD patients.…”
Section: Reward Deficiency Syndrome Index (Rdsi) and Geneticsmentioning
confidence: 92%
See 2 more Smart Citations
“…The statistical analyses found the OR, 95% CI for OR, and a post-risk for 8% estimation of the population's alcoholism prevalence showed a significant detection. The OR results indicated significance for COMT, OPRM1, DRD2, DRD3, DRD4, DAT1, and 5HTT at 5% (Blum et al 2018 , 2020 , 2021 ; Blum et al 2022a , b ; Blum et al 2022a , b ; Fried et al 2020 ; Moran et al 2021 ; Bajaj et al 2022 ; Dennen et al 2022 ; Gondré-Lewis et al 2022 ; Gupta et al 2022 ; Vereczkei et al 2022 ; Thanos et al 2023a , b ; Thanos et al 2023a , b ). Consequently, this study aimed to explore the most effective pharmacogenomic approach to managing spinal pain in postoperative patients by analyzing potential actionable genetic variants associated with FDA-approved drugs targeting specific receptors, that is, the genes themselves (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%